Relasi Gender dalam Keluarga Jama'ah Tabligh - Anis Hidayatul Imtihanah (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2017)
This article discusses the gender relations specifically observed within the marital lives of Tablighi Jama'at members. The research employed two methods to collect data: semi-structured interviews and in-depth interviews. The gender relations within Tablighi Jama'at are predominantly influenced by the neo-traditionalist concept, emphasizing gender complementarity. This concept maintains that men and women are fundamentally equal and possess equal rights. However, Tablighi Jama'at also promotes a clear division of roles between husbands and wives in their marital lives. The husband is considered the primary breadwinner in the public sphere, while the wife is expected to take on the role of housekeeper in the domestic sphere. As members of Tablighi Jama'at, individuals strive to deepen their understanding of their religion, focusing solely on their devotion to God and the Prophet.